2019
DOI: 10.1111/jdv.15421
|View full text |Cite
|
Sign up to set email alerts
|

Trichoscopic signs in systemic lupus erythematosus: a comparative study with 109 patients and 305 healthy controls

Abstract: Background Hair and scalp involvement in systemic lupus erythematosus (SLE) can manifest as scarring alopecia, non-scarring alopecia or scalp/hair shaft changes without apparent hair loss. While trichoscopic signs in chronic cutaneous lupus are well established, data on SLE patients with normal-looking or non-scarring scalp are limited.Objectives To investigate trichoscopic features of SLE patients without chronic cutaneous scalp lesions and compare the findings with normal controls, as well as determine which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…Remarkably, non-scarring alopecia in SLE has been documented to hold prognostic values for SLE, and its coexistence with CLE may imply a higher risk of translation to SLE [41,42]. Future prospective studies with larger sample sizes are needed to confirm our findings.…”
Section: Discussionmentioning
confidence: 53%
“…Remarkably, non-scarring alopecia in SLE has been documented to hold prognostic values for SLE, and its coexistence with CLE may imply a higher risk of translation to SLE [41,42]. Future prospective studies with larger sample sizes are needed to confirm our findings.…”
Section: Discussionmentioning
confidence: 53%
“…2,4,5,8,9,21,22 In a recent study, the presence of certain trichoscopic features in patients with SLE was found to correlate with disease severity; patients with hair shaft changes (including decreased number of hairs, decreased diameter, and hypopigmentation) had more active systemic disease, as determined by significantly higher mean Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) scores, than those without these trichoscopic features. 23 Non-scarring alopecia of SLE may assume a diffuse, patchy, or "lupus hair" pattern. 5 It therefore must be distinguished from telogen effluvium or AA which may also occur concomitantly with SLE.…”
Section: Le-specific Alopecia Discoid Lupus Erythematosus (Dle)mentioning
confidence: 99%
“…Hair and scalp dermoscopy, also known as trichoscopy, has become a standard evaluation for alopecia and other scalp disorders (14). Currently, trichoscopic features among CTDs have been well described and may indicate their diagnostic and prognostic values (15)(16)(17)(18)(19). Onychoscopy refers to the examination of the nail unit using dermoscopy.…”
Section: Introductionmentioning
confidence: 99%